PIAGAM MADINAH DAN KONSEP DEMOKRASI MODERN ISLAM MASA KLASIK - Shobahah, Nurush (Ahkam: Jurnal Hukum Islam, 2019)
ABSTRACTAt present, the state system is increasingly advanced as the result of the adaptation to the world changes. The concept of democracy as one of the current democratic systems is also increasingly sophisticated compared to the practice of democracy in Greek civilization. However, people in developing countries, believes that a good state system which must be implemented in their country is constitutional systems originating from the West which are identical to non-Muslims system. The golden discourses of Islamic civilization in the state are still minimal. Therefore, this article seeks to present a new perspective on the concept of modern democracy which has long been practiced in the classical Islam by the Prophet Muhammad. This current study is a qualitative study which is explaining the concept of Islamic democracy in the classical era compared to the concept of democracy. The data are obtained from examining various books. The results suggest that the Medina charter was an outward proof of the practice of modern democracy that had been carried out by Islam in the classical period.Keywords: Medina Charter, Democracy, Modern,Islamic, Classical